EMPLOYMENT POSSIBILITIES IN RURAL AREAS OF SERBIA THE FACTOR OF PRODUCTION INCREMENT AND FOOD EXPORT - Cvijanović, Drago; Vlahović, Branislav; Milić, Dušan (Economics of Agriculture, 2007)
The resources which are situated in rural areas of Serbia, like as: housing structure, cooperative movement halls and other unused rural objects, production objects for agricultural and other aspects of production, health resorts (spa centers), which are not yet, or are just partly functionable, mountains, rivers, various touristic objects, cultur-historical objects and healthy environment represent very significant and specific potential for further development and employment. This paperwork is an attemp of possible empoyment in serbian rural areas perception, with a view to production increment and food export, as through direct export of agricultural-nutritive products, so through the development of all tourism aspects with accentuation on foreign guests. Along with rural areas tourism development comes to actualization of significant export earnings, as throughout the food consumption in touristic objects, as well as throughout increased trade turnover, more intensive traffic, activation of cottage industry etc., and all in function to increase employment. To vindicate this hypothesis, there is necessary to make a Project which would show some practically employment possibilities in rural areas of Serbia. The authors of this work suggest the Project context, which could give answers about employment possibilities in serbian rural areas.